Seeds and seedlings vigour in tropical maize inbred lines - Adebisi, M.A.; Kehinde, T.O.; Porbeni, J.B.O.; Oduwaye, O.A.; Biliaminu, K.; Akintunde, S.A. (Plant Breeding and Seed Science, 2012)
Seed and seedling vigour is an aspect of seed quality which affects field establishment and performance. Low maize yields have been reported to be affected by several factors in which poor quality seed with low seed and seedling vigour. Information is scarce on seed and seedling vigour in maize inbred lines developed for tropical environments. Fifteen genotypes of tropical maize (Zea mays L.) inbred lines were evaluated to determine the level of differences in seed and seedling vigour traits, and extent of relationships among traits and their heritability. A substantial amount of genetic variability was found, which suggested that most of the traits under study could be improved through selection and utilized in breeding programs. Positive and signifi- cant interrelationship among seed germination and seedling traits and a positive correlation between seed germination and seed vigour and field emergence showed that these could be given due consideration in crop improvement for seed and seedling vigour. High genotypic coefficient of variation, heritability and genetic advance were obtained for seed germination, seed emergence, shoot length and seedling vigour index I and II, revealing the possibility of improvement in these characters through direct selection. The principal component analysis (PCA) identified seed emergence, shoot length, seedling vigour index I and II and tetrazolium vigour as characters that contributed greatly to variation in seed vigour in the maize inbred lines. Cluster analysis partitioned the genotypes into two groups, with group I consisting of seven genotypes and group II comprised the other eight genotypes, which suggested that hybridization between the two groups could lead to high level of heterosis. Genotype V5 had superior seedling vigour traits compared to other genotypes. Seedling emer- gence, shoot length, seedling vigour index I, seedling vigour index II and tetrazolium vigour are effective characters for good seedling vigour traits in maize inbred lines investigated.